1997
DOI: 10.1074/jbc.272.13.8117
|View full text |Cite
|
Sign up to set email alerts
|

Local Transcriptional Control of Utrophin Expression at the Neuromuscular Synapse

Abstract: Recently, the use of a transgenic mouse model system for Duchenne muscular dystrophy has demonstrated the ability of utrophin to functionally replace dystrophin and alleviate the muscle pathology (see Tinsley, J. M., Potter, A. C., Phelps, S. R., Fisher, R., Trickett, J. I., and Davies, K. E. (1996) Nature 384, 349 -353). However, there is currently a clear lack of information concerning the regulatory mechanisms presiding over utrophin expression during normal myogenesis and synaptogenesis. Using in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 33 publications
3
70
0
Order By: Relevance
“…Direct gene transfer was performed on mouse soleus muscles as described in detail elsewhere (8,9,17). The soleus muscles were isolated and injected with 10 l of a solution containing the appropriate plasmids (utrophin A promoter, pCnA* and pCAT) diluted at a concentration of 2-4 g͞l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct gene transfer was performed on mouse soleus muscles as described in detail elsewhere (8,9,17). The soleus muscles were isolated and injected with 10 l of a solution containing the appropriate plasmids (utrophin A promoter, pCnA* and pCAT) diluted at a concentration of 2-4 g͞l.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, muscle denervation (5) as well as regeneration have been shown to also affect expression of utrophin (6,7). In this context, several laboratories have now identified specific transcription factors and promoter elements that are important for regulating the abundance and localization of utrophin transcripts within muscle fibers (8)(9)(10)(11)(12)(13)(14)(15). Of particular relevance, it was shown recently that utrophin can be transcribed from two different promoters, resulting in the expression of utrophin A and B transcripts that differ in their 5Ј end (16).…”
mentioning
confidence: 99%
“…A better understanding of these mechanisms appears important particularly since up-regulation of utrophin is currently envisaged as a therapeutic strategy to prevent the relentless progression of DMD (24,25). In this context, we have recently shown that the nerve exerts a profound influence on utrophin gene expression (26). Since our previous experiments also demonstrated that nerve-derived electrical activity is not a key factor regulating utrophin expression (27), we postulated in these initial studies that nervederived trophic factors likely mediate the local transcriptional activation of the utrophin gene within nuclei of the postsynaptic membrane domain (26).…”
Section: Duchenne Muscular Dystrophy (Dmd)mentioning
confidence: 99%
“…Three-to 4-wk-old C57BL/6 mice were anesthetized, and anterior portions of both lower hindlimbs were shaved and disinfected. The underlying TA muscles were then directly injected with 25 l of DNA solution as described previously (Gramolini et al, 1997;Chakkalakal et al, 2003). The DNA solution contained equal amounts of the 1.3-kb human utrophin-A promoter-reporter (LacZ) construct (see Gramolini et al, 1997;Chakkalakal et al, 2003), the pPUBF⌬N-box construct (luciferase), a constitutively expressed chloramphenicol acetyl transferase (CAT) plasmid (to control for transduction efficiency), and either the ERF expression plasmid or its control (pSG5).…”
Section: Direct Gene Transfermentioning
confidence: 99%